Pengaruh Activity Ratio, Working Capital Management, Firm Size Dan Leverage Ratio Terhadap Profitability Pada Perusahaan Sub Sektor Property Dan Real Estate Yang Terdaftar Dalam Bursa Efek Indonesia - Lionardi, Nadia (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research was to determine the effect of activity ratio, working capital management, firm size and leverage ratio to company’s profitability in sub sector property and real estate listed in Indonesia Stock Exchange. The sampling method was done by using purposive sampling. Secondary data collection methods were taken from IDX published financial statements. This research used multiple regression analysis with random effect method to test their hypothesis using Eviews 6. The results show that activity ratio, firm size and leverage ratio have a positive significant affect to company’s profitability measured using ROE, while working capital management has a negative insignificant affect to company’s profitability. F-test result show that all independent variables in this research simultaneously have a significant effect to company’s profitability in sub sector property and real estate listed in Indonesia Stock Exchange. In the test of Adjusted R2, the analysis results showed that 39,83% profitability was influenced by the independent variables of this research while the remaining 60,17% influenced by other factors not studied.